1999
DOI: 10.1098/rspb.1999.0742
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trade–offs in caddis flies: increased investment in larval defence alters adult resource allocation

Abstract: Developmental trade-o¡s in resource allocation across life-history stages and between di¡erent body parts are predicted by life-history theories. However, there is very little empirical evidence that these occur. We investigated these trade-o¡s in caddis £ies by experimentally manipulating larval case construction and thereby silk expenditure. Case building diverts protein resources away from larval stores, which are of major importance to adult development in species with little or no adult feeding. We induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 24 publications
5
93
1
1
Order By: Relevance
“…Larval reserves were largely found in the head^thorax fraction, which can be roughly approximated to the resources allocated to growth and somatic maintenance on emergence (Boggs 1981;Karlsson 1994;Stevens et al 1999), while only a small percentage was recovered from the abdomen. In contrast, most of the adult food ingested was recovered from the abdominal fraction and from the eggs, con¢rming the predominant role of host feeding in egg production in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Larval reserves were largely found in the head^thorax fraction, which can be roughly approximated to the resources allocated to growth and somatic maintenance on emergence (Boggs 1981;Karlsson 1994;Stevens et al 1999), while only a small percentage was recovered from the abdomen. In contrast, most of the adult food ingested was recovered from the abdominal fraction and from the eggs, con¢rming the predominant role of host feeding in egg production in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Because of a mutual trade-off, the adult mass of cocoon-spinning insects is influenced by the amount of silk used in constructing the pupal case (Stevens et al, 1999). Therefore, the balance between economy and robustness of cocoons is important for cocoon-spinning insects.…”
Section: Discussionmentioning
confidence: 99%
“…Because most caddisfly adults feed minimally or not at all (Mosely, 1939), the acquisition of resources during the larval stage is crucial for growth, case construction, reproduction and maintenance. Several studies have shown that larvae forced to rebuild a case experience a severe increase in energy expenditure, and such an increase can impact the dispersal and reproductive capacities of the adults [Caddisfly (Stevens et al, 1999;Stevens et al, 2000;Jannot et al, 2007), Chironomid (McKie, 2004)]. In a previous study, we found that larvae of Limnephilus rhombicus Linnaeus (Trichoptera: Limnephilidae) forced to rebuild a case increased their oxygen consumption by 50% during the period of reconstruction, compared with control larvae (Mondy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tseng et al, 2011) and/or more rarely serve as signals (reviewed in Schaedelin and Taborsky, 2009). Several studies have already evaluated the cost of secretion of the material from which the structures are made (Eisner, 1994;Stevens et al, 1999;McKie, 2004;Hansell, 2005;Mondy et al, 2011) and the energetic costs, which include metabolic energy expended gathering materials and building the structure (Abarca and Boege, 2011;Mondy et al, 2011). However, the non-energetic costs of construction behaviour remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%